2014
DOI: 10.15277/bjdvd.2014.011
|View full text |Cite
|
Sign up to set email alerts
|

HHS – full or prophylactic anticoagulation?

Abstract: Diabetes mellitus and, in particular, the hyperosmolarity associated with the hyperosmolar hyperglycaemic state (HHS) is associated with an increased risk of thrombotic events. This risk is acknowledged by the authors of the national HHS guideline who recommend prophylactic low molecular weight heparin (LMWH) for all patients with HHS for the full duration of their admission.We present a case of fatal pulmonary embolism in a 39year old man admitted with HHS who was treated according to local hospital trust and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Unfortunately, there are no randomized trials comparing risk-benefit profile of prophylactic and full dose of LMWH. Case reports of thrombotic fatalities under prophylactic dose of LMWH may support the use of full LMWH dose in those with HHS and low hemorrhage risk [77]. Furthermore, Keenan et al demonstrated that thrombotic risk is increased for three months after discharge, with one third of venous thromboembolism events occurring in that period [75].…”
Section: Hypocoagulationmentioning
confidence: 96%
“…Unfortunately, there are no randomized trials comparing risk-benefit profile of prophylactic and full dose of LMWH. Case reports of thrombotic fatalities under prophylactic dose of LMWH may support the use of full LMWH dose in those with HHS and low hemorrhage risk [77]. Furthermore, Keenan et al demonstrated that thrombotic risk is increased for three months after discharge, with one third of venous thromboembolism events occurring in that period [75].…”
Section: Hypocoagulationmentioning
confidence: 96%
“…Whilst thrombotic complications such as myocardial infarction, stroke or peripheral arterial thrombosis occur more frequently in HHS, it is not known whether or not these can be prevented by prophylaxis with low dose LMWH or anti-platelet therapy, or if a full therapeutic dose should be used. 36,37 Having diabetes is associated with an increased risk of developing venous thromboembolic disease (VTE). 38 People with HHS have an increased risk of arterial and VTE.…”
Section: Anticoagulationmentioning
confidence: 99%
“…Whilst thrombotic complications such as myocardial infarction, stroke or peripheral arterial thrombosis occur more frequently in HHS, it is not known whether or not these can be prevented by prophylaxis with low dose LMWH or anti‐platelet therapy, or if a full therapeutic dose should be used. 36 , 37 …”
Section: Managementmentioning
confidence: 99%